M-BIM: a new tool for the Galleria dell’Accademia di Firenze - Grazia Tucci; Alessandro Conti; Lidia Fiorini; Manuela Corongiu; Noemi Valdambrini; Carlotta Matta (Virtual Archaeology Review)
The paper deals with an ongoing research activity for developing a Building Information Model (BIM) for the facility and collections management of museums. The BIM success lies not only in its application for the design and construction of buildings but also because it helps the information management of a building throughout its life cycle. Compared to other activities, in museums management, the container/content relationship is essential for the preventive conservation of artworks, according to national and international guidelines. Then, an effective BIM-based museum information system linked to external databases (called M-BIM) should include also the art collections for managing information regarding both the building and artworks by 3D objects handling. This facilitates the management of the procedures prescribed by international best practices (as the facility and conservation reports set up for the loan of artworks) or by Italian regulations (as to check the compliance of a museum with the minimum standards or to archive renovations and temporary exhibitions). The proposed methodology has been tested on the Galleria dell’Accademia di Firenze (Florence, Italy), situated in a complex heritage building. Starting from data acquired during a laser scanner survey carried out in 2011, a HBIM of the whole building has been created. Then, the sculptures and paintings of a consistent part of the museum have been modelled with different approaches and inserted as BIM objects. Artworks instances include 3D geometry and physical data (dimensions, materials, weight, etc.), other data are obtained from links to already existing external catalogues. A database conceptual model has been formalised, according to INSPIRE Consolidated Unified Modelling Language (UML) of the INSPIRE Directive, with the aim to maintain the independence of the BIM approach but improving data connection with other databases and sources.